Analisis Rasio Keuangan dan Free Cash Flow terhadap Investment Opportunity Set (IOS) dengan Pendekatan Siklus Usaha Studi Pada Emiten Sektor Manufaktur - Setiawan, Rian; Hendrawan, Riko Hendrawan (Business and Management Review, 2010)
The objective of this research is to analyse influence of liquidity, profitability, activity, solvency ratios and free cash flow on investment opportunity set (IOS) in the phases of manufacturing firms’s life cycle. Samples of this research are manufacturing firms listed on the Indonesia Stock Exchange which selected using purposive and random sampling. The size of sample  consists of 33 manufacturing firms selected by random as a representative selection of a population from firms that listed in Indonesia Stock Exchage during 2004-2008 consecutively and classified according to their life cycle’s phase (initial expansion, final exspansion and mature). The analysis method used is multiple liner regression. This research indicates that profitability and activity ratios have significant influence in the initial expansion phase on IOS. In the final expansions phase, profitability ratio and free cash flow have influence on IOS and in the mature phase, only liquidity ratio has influence on IOS. Other result indicated that IOS alter from postive coefficient to a negative coefficient in mature phase as a warning that firm must innovate in order to survive. Therefore, financial ratios and free cash flow can be used as manufacturing firm’s analysis tools at initial expansion, final expansion and mature phases. Keyword: liquidity, profitability, activity, solvency, free cash flow, investment opportunity set, manufacturing firms